The Role of Public Law in Determining the Islamic Calendar in Indonesia - Holis; Ahmad Musadad; Tri Pujiati (Al-Hilal: Journal of Islamic Astronomy, 2025)
The debate over the determination of the beginning of the Islamic calendar in Indonesia is still a complex issue that has a vast impact on religious, social, and public policy aspects. This polemic arises due to differences in ḥisāb (astronomical calculation) and rukyat (hilāl observation) methods adopted by various Islamic organizations, such as Nahdlatul Ulama (NU) and Muhammadiyah. This study used a qualitative approach with descriptive-normative analysis to explore the urgency of legal formalization and the supremacy of public law in determining the beginning of the Islamic calendar. The findings show that the absence of a binding legal authority is the main factor fuelling disagreement. Government-organised isbat sessions are often not universally accepted, so a more assertive legal policy based on national consensus is needed. By considering the principle of benefit, this study recommends the integration of sharia, astronomical technology, and positive law to improve accuracy, legitimacy, and uniformity in determining the beginning of the Islamic calendar.